1991
DOI: 10.1111/j.1460-9568.1991.tb00815.x
|View full text |Cite
|
Sign up to set email alerts
|

Very Slow Retrograde and Wallerian Degeneration in the CNS of C57BL/Ola Mice

Abstract: Wallerian degeneration following peripheral nerve transection in C57BL/Ola mice is very slow in comparison to other strains of mice. We show that following optic nerve transection, the axons of retinal ganglion cells in C57BL/Ola mice undergo very slow Wallerian degeneration and that retrograde degeneration of the ganglion cell bodies is much slower than in other strains of mice. The results suggest that the gene product affecting Wallerian degeneration in the peripheral nervous system (PNS) also confers a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
83
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 14 publications
6
83
0
Order By: Relevance
“…We found that administration of a CD200R1 agonist attenuated disease in a chronic MS model (66). Enhanced CD200 expression was associated with reduced Wallerian degeneration in the slow Wallerian degeneration (Wld s ) mouse (67), a spontaneously occurring mutant with the unique phenotype of protection against several forms of axonal injury (68)(69)(70)(71). In vitro, Wld s neuronal cultures were protected from microglia-induced neurotoxicity, which was abrogated by anti-CD200 antibody treatment (67).…”
Section: Immune Cells Involved In Neurodegenerationmentioning
confidence: 92%
“…We found that administration of a CD200R1 agonist attenuated disease in a chronic MS model (66). Enhanced CD200 expression was associated with reduced Wallerian degeneration in the slow Wallerian degeneration (Wld s ) mouse (67), a spontaneously occurring mutant with the unique phenotype of protection against several forms of axonal injury (68)(69)(70)(71). In vitro, Wld s neuronal cultures were protected from microglia-induced neurotoxicity, which was abrogated by anti-CD200 antibody treatment (67).…”
Section: Immune Cells Involved In Neurodegenerationmentioning
confidence: 92%
“…Projections of central neurons are also protected after lesions of axonal fiber tracts in Wld s mice, including the perforant path of the hippocampal formation and optic nerve (Perry et al, 1991;Shi and Stanfield, 1996). Less evident is whether Wld is associated with neuronal preservation more generally in the central nervous system (Ludwin and Bisby, 1992).…”
mentioning
confidence: 97%
“…The Wlds mutant mouse that overexpresses a slow Wallerian degeneration protein (WldS), a fusion protein composed of the N-terminal 70 amino acids of ubiquitination factor E4 linked to full-length Nmnat1 exhibits slow axonal Wallerian degeneration in response to nerve injury in the peripheral nervous system (PNS). This WldS fusion protein protects axons from degeneration initiated by a variety of insults both in vitro and in vivo (15)(16)(17). Further, it has been shown in multiple axonal injury paradigms that expression of Nmnat1 robustly protects axons in vitro and in vivo in the PNS (18)(19)(20).…”
mentioning
confidence: 99%